P52 The relationship of vitamin D levels with disease activity in systemic lupus erythematosus. (23rd March 2020) - Athanassiou, Lambros; Kostoglou, Ifigenia; Tsakiridis, Pavlos; Tzanavari, Aikaterini; Devetzi, Eirini; Gatsiou, Marina; Koutsilieris, Michael; Athanassiou, Panagiotis
Abstract : Background: Vitamin D is known to exert a potent immunomodulatory action. It has immunostimulatory properties and in parallel exerts immunosuppression and inhibits tissue destruction related to autoimmunity. Vitamin D deficiency, thus, is related to immune activation and the development of autoimmune diseases. Systemic lupus erythematosus (SLE) is an autoimmune disease affecting all organ systems. It develops in all age groups, however young female patients are particularly vulnerable. Vitamin D status is currently assessed by the measurement of 25(OH)D3 levels. The aim was to assess vitamin D levels in a cohort of SLE patients and examine the relationship of vitamin D levels with disease activity. Measurements were also performed in a control group. Methods: In a cohort of 30 SLE patients, 27 female and 3 male and a control group 25(OH)D3 levels were measured. In all SLE patients clinical and laboratory examination was performed to assess the activity of the disease. Serum inflammation markers were measured. 25(OH)D3 levels were measured by radioimmunoassay. The measurement of 25(OH)D3 was performed in a two-step procedure. The first step aimed at rapid extraction of 25(OH)D and other hydroxylated metabolites from serum or plasma with acetonitrile. Following extraction, samples were assayed by competitive RIA using an antibody with specificity to 25OHD. The sample, antibody and tracer were incubated for 90 min at 20–25 °C. Phase separation was accomplished after 20 min incubation at 20–25 °C with a second antibody precipitating complex. The sensitivity of the assay was <1.6 ng/ml and the recovery approximately 100% for 25(OH)D3 . Within and between batch precision was <12% and <11%, respectively. Results: Serum 25(OH)D3 levels were significantly lower in SLE patients than in the control group (p<0.001, Student's t test). An inverse relationship was observed between inflammation markers and 25(OH)D3 levels, lower 25(OH)D3 levels observed in SLE patients with high inflammation markers. Conclusions: Vitamin D insufficiency or frank deficiency has been observed in patients with autoimmune diseases, such as rheumatoid arthritis. Low vitamin D levels have also been observed in SLE patients. In the described cohort of SLE patients low vitamin D levels were observed and there was an inverse relationship between vitamin D levels and disease activity. In view of the fact that SLE patients display photosensitivity and are advised to avoid sun exposure, these findings denote that 25(OH)D3 levels should be measured in SLE and that patients should be supplemented with cholecalciferol as the hormone has immune modulating properties.